Spillover effects of Japan's quantitative and qualitative easing on East Asian economies - Shin'ichi Fukuda (Asian Development Bank Institute (ADBI), 2017)
This paper explores the spillover effects of Japan's quantitative and qualitative easing (QQE) on East Asian economies. Under the new monetary policy regime, the Japanese yen depreciated substantially, raising concerns that it would have a regional beggar-thy-neighbor effect. It is thus important to see what effects the QQE had on neighboring economies. Our empirical investigation of East Asian stock markets finds that they first reacted to the yen's depreciation negatively, yet came to respond positively as the QQE progressed, implying that the QQE had a much smaller beggar-thy-neighbor effect than was originally feared. We show that the QQE benefited East Asian economies because the positive spillover effect of Japan's stock market recovery dominated the beggar-thy-neighbor effect in the region.
Keywords: F10; F32; E52; 330; spillovers; quantitative and qualitative easing; qqe; beggar-thy-neighbor effect; East Asia; yen depreciation; stock market